Evaluation of nanostructured electrode materials for high-performance supercapacitors using multiple-criteria decision-making approach - Ibrahim M. Hezam; Aref M. Al-Syadi; Abdelaziz Foul; Ahmad Alshamrani; Jeonghwan Gwak (Electronic Research Archive, 2023)
The enhancement of electrode materials' properties for improving mercantile supercapacitors' performances is a remarkable research area. Throughout recent years, a significant amount of research has been devoted to improving the electrochemical performance of supercapacitors via the improvement of novel electrode materials. The nanocomposite structure provides a greater specific surface area (SSA) and lower ion/electron diffusion tracks, consequently enhancing supercapacitors' energy density and specific capacitance. These significant properties offer a wide range of potential for the electrode materials to be applied in diverse applications. For instance, their applications are in portable electronic systems such as all-solid-state supercapacitors, flexible/transparent supercapacitors and hybrid supercapacitors. The authors of this paper introduced a multi-criteria model to assess the priority of nanostructured electrode materials (NEMs) for high-performance supercapacitors (HPSCs). This work combines Analytic Hierarchy Process (AHP) with the Evaluation Based on Distance from Average Solution (EDAS) and Grey Relational Analysis (GRA) methods. Herein, the rough concept addresses the uncertainties resulting from the group decision-making process and the vague values of the properties of the NEMs. The modified R-AHP method was employed to find the criteria weights based on the multi-experts' opinions. The results reveal that specific capacitance (SC) and energy density (ED) are the most important criteria. R-AHP was integrated with R-EDAS and R-GRA models to evaluate the fourteen NEMs. The results of the R-EDAS method were compared with those provided by the R-GRA method. The results of the proposed integrated approach confirmed that it results in reliable and reputable ranks that will provide a framework for further applications and help physicists find optimal materials by evaluating various alternatives.